Hyperbranched Polyimides Prepared from 4,4 ́,4 ́ ́-Triaminotriphenylmethane and Mixed Matrix Materials Based on Them - Minko, Evgenia; Sysel, Petr; Spergl, Martin; Slapakova, Petra (IntechOpen, 2012)
None